Simultaneous Modeling of Young’s Modulus, Yield Stress, and Rupture Strain of Gelatin/Cellulose Acetate Microfibrous/Nanofibrous Scaffolds Using RSM - Barazesh, Alireza; Navidbakhsh, Mahdi; Abouei Mehrizi, Ali; Koosha, Mojtaba; Razavi Bazaz, Sajad; Li, Tianduo (Frontiers in Bioengineering and Biotechnology, 2021)
Electrospinning is a promising method to fabricate bioengineered scaffolds thanks to utilizing various types of biopolymers, flexible structure, and also the diversity of output properties. Mechanical properties are one of the major components of scaffold design to fabricate an efficacious artificial substitute for natural extracellular matrix. Additionally, fiber orientations, as one of the scaffold structural parameters, could play a crucial role in the application of fabricated fibrous scaffold. In this study, gelatin was used as a highly biocompatible polymer in blend with Cellulose acetate, a polysaccharide, to enhance the achievable range of mechanical characteristics to fabricated fibrous electrospun scaffolds. By altering input variables, such as polymers concentration, weight ratio, and mandrel rotation speed, scaffolds with various mechanical and morphological properties could be achieved. As expected, the electrospun scaffold with higher mandrel rotation speed, shows higher fiber alignment. Wide range of mechanical properties gained through different values of polymer ratio and total concentration. A general improve in mechanical strength was observed by increasing concentration and cellulose acetate content in the solution, but contradictory effects, such as high viscosity in more concentrated solution, influenced the mechanical characteristics as well. A response surface method (RSM) was applied on experimental results in order to describe a continuous variation of Young’s modulus, yield stress, and strain at rupture. A full quadratic version of equations with 95% confidence level was applied for the response modeling. This model would be an aid for engineers to adjust mandrel rotation speed, solution concentration, and gelatin/cellulose acetate ratio to achieve desired mechanical and structural properties.